2017
DOI: 10.11002/kjfp.2017.24.7.975
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity and physicochemical composition of fermented Vigna angularis using Bacillus subtilis KCCM 11965P

Abstract: Health of human intestine has deteriorated due to excessive stress and western diet. In this study, Vigna angularis was fermented by Bacillus subtilis KCCM11965P in order to develop prebiotic resource for improving bowel movement. The contents of ash and crude protein were 3.35±0.04% and 21.1±0.19% respectively. Vigna angularis extract (1, 3, 5%) were incubated with 3% (v/v) Bacillus subtilis KCCM 11965P for 0, 24, 48, and 72 h. Total bacterial numbers showed that the combination of 3% powdered seeds and 72 h … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Bacillus subtilis, which is commonly found in Korean traditional fermented soybean products, is a microorganism generally recognized as safe (GRAS). It has been reported that in the fermentation process, B. subtilis produces various enzymes such as protein and carbohydrate hydrolytic enzymes, as well as physiologically active substances such as functional peptides and c-polyglutamic acid (PGA), a viscous sticky mucilage of amino acid or sugar [18,19]. Tanimoto et al [20] reported that PGA, which is a polymer with water-holding capacity produced by B. subtilis, not only increases calcium solubility in the lower small intestine as it has a low pH, but also potentially prevents osteoporosis by delaying intestinal transit time and facilitating intestinal calcium absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Bacillus subtilis, which is commonly found in Korean traditional fermented soybean products, is a microorganism generally recognized as safe (GRAS). It has been reported that in the fermentation process, B. subtilis produces various enzymes such as protein and carbohydrate hydrolytic enzymes, as well as physiologically active substances such as functional peptides and c-polyglutamic acid (PGA), a viscous sticky mucilage of amino acid or sugar [18,19]. Tanimoto et al [20] reported that PGA, which is a polymer with water-holding capacity produced by B. subtilis, not only increases calcium solubility in the lower small intestine as it has a low pH, but also potentially prevents osteoporosis by delaying intestinal transit time and facilitating intestinal calcium absorption.…”
Section: Introductionmentioning
confidence: 99%